Employability Skills and Career Readiness Among Muslim Vocational Students: Mediating Role of Career Decision-Making Self-Efficacy - Wenny Wulandari; Arif Sahin; Wise Rahmawan; Farouq Fathurrahman; Muh. Azhar Mubarak; Wiffy Zalina Putri (Pamomong: Journal of Islamic Educational Counseling, 2026)
Rapid changes in the labour market require vocational students to develop career readiness supported by employability skills and psychological resources for career decision-making. This study tested the direct and indirect effects of employability skills on career readiness via Career Decision-Making Self-Efficacy (CDMSE) among Grade-12 Muslim vocational students. Using a cross-sectional design, all students at SMK Multicomp Depok, Indonesia (N = 215) were surveyed using saturated sampling, with Muslim status verified through school records. Adapted measures were used: the Self-Perceived Employability Scale (α = .96), the Career Decision-Making Self-Efficacy Scale (α = .95), and the Student Career Readiness Scale (α = .98). Mediation was examined using PROCESS Macro for SPSS (Model 4) with bootstrap resampling. Employability skills significantly predicted CDMSE (b = 1.21, SE = .12, t = 10.22, p < .01; R² = .33) and career readiness (direct effect controlling for CDMSE: b = .66, SE = .11, t = 6.09, p < .01). CDMSE also significantly predicted career readiness (b = .42, SE = .05, t = 8.13, p < .01; model R² = .53). The indirect effect of employability skills on career readiness via CDMSE was significant (b = .51, SE = .09, 95% BC CI [.35, .70]), indicating partial mediation. The findings support Social Cognitive Career Theory and suggest that guidance and counseling programs should integrate employability development with interventions that strengthen decision-making self-efficacy. Limitations include the cross-sectional design, self-report measures, and a single-school sample; future research should use longitudinal designs and broader settings to improve generalizability.